Glyceraldehyde‐3‐phosphate dehydrogenase promotes liver tumorigenesis by modulating phosphoglycerate dehydrogenase. Issue 2 (19th June 2017) - Liu, Shanshan; Sun, Yu; Jiang, Ming; Li, Yangkai; Tian, Ye; Xue, Weili; Ding, Ninghe; Sun, Yue; Cheng, Cheng; Li, Jianshuang; Miao, Xiaoping; Liu, Xinran; et al.
Abstract : Up‐regulated glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) is observed in multiple cancers with unclear mechanism. Using GAPDH transgenic mouse and a mouse model of diethylnitrosamine‐induced hepatocellular carcinoma (HCC), here we show that GAPDH overexpression aggravated tumor development by activating cell proliferation and inflammation. In cultured hepatic cells, overexpression of GAPDH or a catalytic domain‐deleted GAPDH (GAPDH ΔCD ) affected metabolism, up‐regulated phosphoglycerate dehydrogenase (PHGDH), increased histone methylation levels, and promoted proliferation. Consistently, inhibition of GAPDH by short hairpin RNA reprogrammed metabolism down‐regulated PHGDH and histone methylation, and inhibited proliferation. The xenograft study suggested that HepG2 cells overexpressing GAPDH or GAPDH ΔCD similarly promoted tumor development, whereas knockdown PHGDH in GAPDH overexpressing cells significantly inhibited tumor development. In liver sections of HCC patients, increased GAPDH staining was found to be positively correlated with PHGDH and histone methylation staining. Conclusion: GAPDH increases histone methylation levels by up‐regulating PHGDH, promoting diversion from glycolysis to serine biosynthesis, and consequently accelerating HCC development. (Hepatology 2017;66:631–645).